Interplay Between JSRV, an Oncogenic Retrovirus, and the Pulmonary Epithelium - Archer, Fabienne; Mornex, Jean-Francois; Leroux, Caroline (Current Immunology Reviews (Discontinued), 2012)
Jaagsiekte sheep retrovirus (JSRV) is a retrovirus which infects small ruminants and is responsible for a natural lung cancer. This virus bears an oncogenic envelope inducing epithelial cell transformation from the deep lung. The cells, main target of the infection and constitutive of the tumors, are alveolar type II cells in the alveoli and Clara cells in the bronchioli. The immune response to JSRV infection is poorly understood. The specific humoral response is limited and the cell-mediated response is marked by CD4+ lymphocytopenia, neutrophilia, and macrophage invasion of the tumor. The mechanisms of viral immune evasion could be explained by the direct and indirect immunosuppressive effects of the virus, and by the immune tolerance of the infected hosts due to the presence in the sheep genome of endogenous viral forms (enJSRV).
Keywords: alveolar type II cells